Crime ambiental e ecopedagogia - Rowedder, Vania Trajano (2020)
To ensure the right to an ecologically balanced environment and the common usage of the environmental resources for the society, the need for practicing environmental management arises. This mediation process executed by environmental management continuously defines and redefines the way that different damage causers, by its practices. In this context, the present work aims to evaluate the fined environmental crimes at the Special Criminal Forum of Toledo – PR, during the period of 2000 and 2019, as a way of environmental protection. Nowadays, it is registered 300 lawsuits in total, however, there are 60 lawsuits available for public consultation. Their analysis showed that the major incidence of environmental analysis is related to Fauna, mainly, referring to mistreat crimes against animals. But with the remaining lawsuits in secrecy of justice, the presence of other types of crimes is imaginable. In this sense, by penal transaction, the environmental crimes registered at the JECRIM, were resolved by cash benefit, this being the index means of sentence of extinction of punishment, due to the fulfillment of the same. This reflects positively when analyzing the few causes for revocation of proposed criminal transactions. The data also showed that the participation of society as an inspection body for environmental crimes, through denunciation, contributed significantly for these crimes to come to the attention of the Judiciary. Therefore, in view of the results obtained, together with Law No. 9.605/1998, we defend that Eco pedagogy can contribute with alternatives to regulate criminal and administrative sanctions derived from conducts and activities that are harmful to the environment.